Penegakan Hukum Pidana Terhadap Lembaga Pengumpul Zakat yang Tidak Memiliki Izin di Sumatera Barat - Afdilla, Andra; Zurnetti, Aria; Yasniwati, Yasniwati (LPPM Universitas Ekasakti Padang, 2024)
Abstract: The Government of the Republic of Indonesia through Law Number 23 Year 2011 on Zakat Management prohibits unauthorized institutions to collect zakat because it has the potential to misuse the collected zakat funds. The collection of zakat funds by unauthorized institutions in West Sumatra Province has the effect of losing public trust in making zakat payments and zakat funds that have been collected by unauthorized institutions have the potential to fund other criminal activities such as terrorism movements that threaten the sovereignty of the Republic of Indonesia. The formulation of this research problem are: (1) How is the criminal law enforcement against unauthorized zakat collecting institution based on Law Number 23 Year 2011 on Zakat Management by law enforcement officials in West Sumatera? 2) How are the efforts that have been made in law enforcement against criminal acts of zakat management by unauthorized zakat collecting institution in West Sumatera? This research was conducted with sociological juridical research methods and the data sources of this research were primary data and secondary data, data collection techniques were carried out by interview and analyzed qualitatively. The conclusions of this study are 1) Criminal law enforcement against unlicensed zakat collection institutions based on Law number 23 of 2011 concerning zakat management by law enforcement officials in West Sumatra is carried out by the West Sumatra Regional Police which is influenced by legal factors, law enforcers, facilities, society, and culture. 2) Efforts that have been made in criminal law enforcement against unlicensed zakat collection institutions based on Law number 23 of 2011 concerning zakat management in West Sumatra are penal efforts and non-penal efforts (Socialization). Keyword: Zakat, Law Enforcement, Crime, Illegal Institution